Rumuńska choroba na śmierć. Kilka uwag o hermeneutyce cielesności (na przykładzie prozy Maxa Blechera) - Szymankiewicz, Błażej (Przestrzenie Teorii, 2019)
In the European literature and culture of the interwar period we can observe increased interest in the physicality and the process of dying. Novels which touch upon these subjects are described by some scholars and critics as “sanitarian literature”. The following text is discussing the issues of the works of Max Blecher; his novel “Scarred Hearts” can be included in the circle of mentioned “sanitarian literature”. Blecher’s novel presents certain strategies of dealing with a terminal illness and the finiteness of human existence, as well as the alientation associated with these. The most frequently cited interpretive trail in this case is the philosophy of Kierkegaard, Jaspers and Heidegger. In the first part of the article, I refer to Blecher’s biography and his reception, while in the next part I contrast selected excerpts from his novel with philosophical hermeneutics.